2009
DOI: 10.1016/j.immuni.2009.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Interleukin-17A and -17F Is Coupled to T Cell Receptor Signaling via Inducible T Cell Kinase

Abstract: Th17 cells play major roles in autoimmunity and bacterial infections, yet how T cell receptor (TCR) signaling affects Th17 differentiation is relatively unknown. We demonstrate that CD4+ T cells deficient in Itk, a tyrosine kinase required for full TCR-induced activation of PLC-γ, exhibit decreased IL-17A expression, yet relatively normal expression of RORγT, RORα and IL-17F. IL-17A expression was rescued by pharmacologically-induced Ca2+ influx or expression of activated NFATc1. Conversely, decreased TCR stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
190
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(208 citation statements)
references
References 51 publications
16
190
1
1
Order By: Relevance
“…1B). The strength of T-cell receptor (TCR) signaling is also known to regulate IL-17 production (28,29). We therefore investigated whether alteration of TCR stimulation could affect the reduced generation of IL-17-producing cells in Menin −/− T-cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…1B). The strength of T-cell receptor (TCR) signaling is also known to regulate IL-17 production (28,29). We therefore investigated whether alteration of TCR stimulation could affect the reduced generation of IL-17-producing cells in Menin −/− T-cell cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of RLK alone has few functional consequences, but deletion of RLK in combination with ITK appears to be important in Th1 cells, where it is preferentially expressed. In addition, the deletion of ITK and RLK has a marked effect on Th17 differentiation and IL-17 production (13). In some settings, it appears that ITK and RLK are redundant signaling molecules because overexpression of RLK in ITK Ϫ/Ϫ mice rescues the Th2 response in a model of asthma (14).…”
Section: Il-2-inducible T-cell Kinase (Itk)mentioning
confidence: 99%
“…In IL-17A knockout (KO) mice, EAE is markedly suppressed, indicating that IL-17 contributes to the development of EAE (33). Although it has been reported that the transcription factors nuclear factor for activated T cells (NFAT), retinoid orphan nuclear receptor ␥t (ROR␥t), and Runt-related transcription factor 1 (Runx1) are important for the T cell receptor (TCR)-mediated transcriptional regulation of IL-17A (24,29,38,74), knowledge of the factors involved in the cellular and molecular regulation of IL-17A remains limited.…”
mentioning
confidence: 99%